2008
DOI: 10.1107/s0907444908009980
|View full text |Cite
|
Sign up to set email alerts
|

Nucleant-mediated protein crystallization with the application of microporous synthetic zeolites

Abstract: Protein crystallization is still a major bottleneck in structural biology. As the current methodology of protein crystallization is a type of screening, it is usually difficult to crystallize important target proteins. It was thought that hetero-epitaxic growth from the surface of a mineral crystal acting as a nucleant would be an effective enhancer of protein crystallization. However, in spite of almost two decades of effort, a generally applicable hetero-epitaxic nucleant for protein crystallization has yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 44 publications
5
56
0
Order By: Relevance
“…S4). Other structural homologs, as identified in an earlier study based on YTHDC1 (13), include the DUF55 domain of human thymocyte nuclear protein 1 (15) and the EVE domain that is found in a collection of prokaryotic proteins (16) such as Pyrococcus horikoshii protein PH1033 (17), Agrobacterium tumefaciens Atu2648 (16), and a Leishmania major protein (18) (Fig. S4), with Z scores between 9 and 13 from the program DaliLite (19) and sequence identities between 10 and 18%.…”
Section: Resultsmentioning
confidence: 99%
“…S4). Other structural homologs, as identified in an earlier study based on YTHDC1 (13), include the DUF55 domain of human thymocyte nuclear protein 1 (15) and the EVE domain that is found in a collection of prokaryotic proteins (16) such as Pyrococcus horikoshii protein PH1033 (17), Agrobacterium tumefaciens Atu2648 (16), and a Leishmania major protein (18) (Fig. S4), with Z scores between 9 and 13 from the program DaliLite (19) and sequence identities between 10 and 18%.…”
Section: Resultsmentioning
confidence: 99%
“…A crystallization drop of 1.0 ”L, in the presence of synthetic zeolite molecular sieves as heteroepitaxic nucleants [40], [41], was created by mixing 1∶1 mixture of 28.0 mg/mL protein solution in 0.02 M MES-NaOH (pH 5.8) and precipitant solution composed of 40% ( w/v ) polyethylene glycol (PEG) 8,000, 0.2 M CaCl 2 , and 0.1 M MES-NaOH (pH 5.8) in a well of a Nunc HLA crystallization plate (Nalge Nunc International) which was then covered with 20 ”L of paraffin oil. The resulting Ao α-amylase crystals were submitted to a heavy-atom derivatization experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The pores promote aggregation of proteins such that a spontaneous critical nucleus comprised of tens of protein molecules form inside each pore. Another study with respect to a porous material has shown that zeolites with regular micropores induce heteroepitactic nucleation [19]. A common feature of these nucleants is that their specific surface properties govern the nucleation potential of the proteins.…”
Section: Introductionmentioning
confidence: 99%